2021
DOI: 10.1002/ccd.29745
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in coronary, vascular, structural, and congenital heart disease

Abstract: Cardiovascular disease (CVD) remains the leading cause of death in the United States. However, percutaneous interventional cardiovascular therapies are often underutilized in Blacks, Hispanics, and women and may contribute to excess morbidity and mortality in these vulnerable populations. The Society for Cardiovascular Angiography and Interventions (SCAI) is committed to reducing racial, ethnic, and sex‐based treatment disparities in interventional cardiology patients. Accordingly, each of the SCAI Clinical In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 151 publications
(154 reference statements)
0
24
0
Order By: Relevance
“…Despite the higher cardiovascular risk for mortality in the HL population compared with whites, especially in those with severe CAC, 1,2 the outcomes in this OA analysis showed no difference between HL and non‐HL patients. Percutaneous interventional cardiovascular therapies are often underutilized in Hispanics and that may contribute to excess morbidity and mortality in this vulnerable population 9,10 . Overall, HL patients are more likely to present with comorbidities, experience longer delays before treatment, and suffer worse outcomes when compared with non‐HL white patients 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the higher cardiovascular risk for mortality in the HL population compared with whites, especially in those with severe CAC, 1,2 the outcomes in this OA analysis showed no difference between HL and non‐HL patients. Percutaneous interventional cardiovascular therapies are often underutilized in Hispanics and that may contribute to excess morbidity and mortality in this vulnerable population 9,10 . Overall, HL patients are more likely to present with comorbidities, experience longer delays before treatment, and suffer worse outcomes when compared with non‐HL white patients 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…The TAVR utilization among underserved and underrepresented populations are lower. This was initially thought to be related to lower incident of AS among Black and Hispanic populations ( 109), but further studies suggested that this might be due to limited accesses to care, low socioeconomic status, and treatment biases in the non-White population (109)(110)(111)(112). This calls the need for advance clinical care accessible to all patients regardless of their race and ethnicity.…”
Section: Valve Replacementmentioning
confidence: 99%
“…During the early era of reperfusion in the USA, door-to-needle (thrombolytic therapy) and door-to-balloon times were significantly longer in Blacks compared to Hispanics or Whites 42 . More recent studies reveal that Black patients with ACS have longer wait times in the emergency department 43 and experience delays in coronary angiography and preferential use of bare metal vs drug-eluting stents 44,45 .…”
Section: Racial and Disparities In The Care Of Acute Coronary Syndromesmentioning
confidence: 99%
“…42 More recent studies reveal that Black patients with ACS have longer wait times in the emergency department 43 and experience delays in coronary angiography and preferential use of bare metal vs drug-eluting stents. 44 , 45 …”
Section: Influence Of Racism and Racial Bias In Cardiovascular Carementioning
confidence: 99%